2011
DOI: 10.1080/09540121.2011.613910
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related stigma within communities of gay men: a literature review

Abstract: While stigma associated with HIV infection is well recognised, there is limited information on the impact of HIV-related stigma between men who have sex with men and within communities of gay men. The consequences of HIV-related stigma can be personal and community-wide, including impacts on mood and emotional well-being, prevention, testing behaviour, and mental and general health. This review of the literature reports a growing division between HIV-positive and HIV-negative gay men, and a fragmentation of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
174
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(193 citation statements)
references
References 47 publications
7
174
0
12
Order By: Relevance
“…The HIV status of study participants was the most frequently addressed HIV subtopic in this review, which may indeed be reflective of the deepening concerns over increasing rates of HIV infection among Black YGBMSM. In contrast, HIV stigma was only explored in two articles, even though many researchers have suggested that stigma related to HIV may be a fundamental driving force behind the epidemic (Maulsby et al, 2014;Smit et al, 2012). Last, HIV treatment knowledge/awareness, linkage/retention in care, and ART use/viral loads/CD4 counts were all poorly represented in this review.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV status of study participants was the most frequently addressed HIV subtopic in this review, which may indeed be reflective of the deepening concerns over increasing rates of HIV infection among Black YGBMSM. In contrast, HIV stigma was only explored in two articles, even though many researchers have suggested that stigma related to HIV may be a fundamental driving force behind the epidemic (Maulsby et al, 2014;Smit et al, 2012). Last, HIV treatment knowledge/awareness, linkage/retention in care, and ART use/viral loads/CD4 counts were all poorly represented in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Although the GRINDR sample did not acquire any biologic specimens for HIV or STI testing, self-reports of HIV-positive serostatus almost universally underestimate the true seroprevalence rate 16 attributable primarily to occult and undiagnosed HIV infection and secondarily to the persistent stigma associated with reporting an HIVpositive diagnosis among MSM. 17 Participants demonstrated a high rate of ongoing transmission-associated risk behavior, indicating that the sample is an excellent target for recruitment for and ultimate deployment of HIV prevention studies and interventions, respectively. In particular, although participants reported low rates of previous clinical trial participation, more than half of participants noted that they would be interested in participating in a future HIV prevention study, with an additional 25 % indicating that they might be interested in participating, depending on the details of the study, incentives, and various other parameters.…”
Section: Discussionmentioning
confidence: 99%
“…It is acceptable in most gay communities to be openly sexual, to have multiple partners, to negotiate openly for sex, and to enjoy sex freely (Bronski, 2000;Crossley, 2004). Given this, there may be less permission for gay (Schope, 2005;Smit et al, 2012;Wierzalis, Barret, Pope, & Rankins, 2006), older MSM may experience a pressure to look attractive and often are expected to be able to follow through on any sexual opportunities that arise. It is also much more acceptable and possible in some gay subcultures to use sex as a way to deal with stress and feelings of isolation (Murray & Adam, 2001).…”
Section: Factors Associated With Unprotected Anal Intercoursementioning
confidence: 99%